Hush : an Irish princess' tale - Napoli, Donna Jo, 1948- (Atheneum Books for Young Readers, 2007)
Fifteen-year-old Melkorka, an Irish princess, is kidnapped by Russian slave traders and not only learns how to survive but to challenge some of the brutality of her captors, who are fascinated by her apparent muteness and the possibility that she is enchanted.